Physical activity levels in children with sensory problems: Cross-sectional analyses from the Millennium Cohort Study. Issue 1 (January 2018) - Williams, Genevieve; Aggio, Daniel; Stubbs, Brendon; Pardhan, Shahina; Gardner, Benjamin; Smith, Lee
Abstract: Background: Hearing and vision impairments/problems are associated with increased risk of premature mortality in adulthood. One potential pathway explaining this association is reduced levels of physical activity. Reductions in activity levels due to sensory impairments may commence earlier in life; however, associations between sensory impairments/problems and activity levels in childhood are not well understood. Objective: The objective of this study was to examine associations between hearing and vision problems and objectively measured activity levels in a representative sample of British children. Methods: Data were drawn from sweep 4 of the Millennium Cohort Study, a prospective cohort study among children aged 7. Child hearing and vision problems were reported by parents in a postal survey. Children were also invited to have their physical activity measured objectively via accelerometry. A total of 6410 children had valid accelerometry data accompanied by complete survey data on the variables of interest. The main outcomes were objectively measured moderate-to-vigorous physical activity, steps and sedentary time. Adjusted linear regression was used to examine associations between vision and hearing problems and objectively measured activity levels. Results: In this sample of 7-year old children, 16.7% (n = 1068) had a reported vision problem and 11.6% (n = 745) had a hearing problem. Reported vision problems in both eyes, but not one eye, was associated with 2 fewer minutes of moderate-to-vigorous physical activity per day (B = −2.1 95% Confidence Intervals [CI] −3.9 to −0.4) and almost 200 fewer steps per day (B = −198.4 95% CI, −398.4 to 1.6). Hearing problems were not associated with activity levels in either one or both ears. Conclusion: Children with visual problems affecting both eyes, but not one eye, are likely to have lower levels of physical activity. Strategies to promote physical activity in children with visual problems are warranted.